Surgical and Visual Outcome for Recurrent Retinal Detachment Surgery - Constantin Pournaras; Chrysanthi Tsika; Catherine Brozou; Miltiadis K. Tsilimbaris (Journal of Ophthalmology)
Purpose. To evaluate the anatomical and functional outcome of repeated surgeries for recurrent retinal detachment. Methods. We retrospectively reviewed 70 cases with refractory retinal detachment of various etiologies that required multiple operations. Anatomical success (attached retina) or failure (totally/partially-detached retina) was assessed biomicroscopically. The BCVA was used for the evaluation of the functional outcome, at presentation and at the end of follow-up. Various pre-, intra-, and postoperative factors were associated with anatomical success or failure as well as with final functionality. Results. The mean number of surgeries was 4 (range: 2 to 10). The anatomical success rate was 80% (56 attached cases, 14 detached cases). 29% of the attached cases had a BCVA better than 20/40 (Snellen chart). The number of operations doesn’t seem to affect significantly the final visual acuity. The PVR was found to affect both the anatomical and functional outcome (P=0.014 & P=0.002, respectively). Conclusions. In the present study, it is suggested that multiple operations for refractory retinal detachment may result in successful anatomic results, with a fare functional outcome at the same time. Eventually, we verified that the existence of PVR worsens the prognosis.